Numerical valuation of surrender options - Boateng, Kwasi (2016)
A thesis submitted to the Department of Mathematics,Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the Degree of Master of Philosophy in Actuarial Science.